Salvia Miltiorrhiza Ameliorates Liver Fibrosis by Activating Hepatic Natural Killer Cells in Vivo and in Vitro - Peng, Yuan; Yang, Tao; Huang, Kai; Shen, Li; Tao, Yanyan; Liu, Chenghai (Frontiers in Pharmacology, 2018)
Natural killer (NK) cells are known for their ability to kill activated hepatic stellate cells (HSCs), which has been confirmed both in patients and animal models. But the killing function is depressed in period of advanced liver injury. Salvia Miltiorrhiza (SM), a Chinese herbal medicine for invigorating blood circulation and eliminating stasis, is widely used to treat liver fibrosis in clinic. Nevertheless, the immunological mechanism remains unclearly. Here, we put forward the hypothesis that the anti-fibrotic effect of SM is concerned with boosting the activation of hepatic NK cells. Liver fibrosis was induced with carbon tetrachloride (CCl4) and effects of SM on NK cells and hepatic stellate cell（JS-1 cell line, HSC）were investigated in vivo and in vitro. Hepatic NK cells were isolated from C57BL/6 mice, and pre-incubated with SM before they were co-cultured with HSCs. We found that SM increased frequency of NK cells, enhanced activities of NKG2D and Nkp46 on NK cells and inhibited activation of HSCs in vivo and in vitro. SM could promote the activities of NK cells by increasing the expressions of NKG2D and IFN-γbefore or after co-cultured with HSCs in vitro. Besides, SM could partially antagonize ASGM-1-induced NK cell depletion and enhance the cell activities to inhibit HSCs activation in vitro. Therefore, our work provided a new insight into the anti-fibrotic mechanism that SM could enhance the activities of NK cell to reduce liver fibrosis in vivo and in vitro.